3rd International Conference on Thermal Issues in Machine Tools (ICTIMT2023) - Ihlenfeldt, Steffen (Lecture Notes in Production Engineering, 2023)
This open access conference proceedings contains all the papers presented at the ICTIMT 2023, the 3rd International Conference on Thermal Issues in Machine Tools. The event takes place in Dresden, the capital of Saxony, from March 21-23 2023. The conference is organized by the Chair of Machine Tools Development and Adaptive Controls of the Technische Universität Dresden. The Editor Prof. Dr.-Ing. Steffen Ihlenfeldt, born 1971 in Aschersleben, studied Mechanical Engineering at the Technische Universität Braunschweig from 1991 to 1997. From 1997 to 1999, he worked as a research assistant in the Department of Machine Tools at the Fraunhofer Institute for Machine Tools and Forming Technology IWU. From 2000 to 2015, he held various management positions at the Fraunhofer IWU Chemnitz, most recently as Head of the Machine Tool Department in the Main Department Machine Tools and Automation. In 2015, Prof. Ihlenfeldt took over as head of the Chair of Machine Tools Development and Adaptive Controls at the Institute of Machine Tools and Control Engineering (IWM) - now the Institute of Mechatronic Engineering (IMD) - at Technische Universität Dresden. Since 2021, Prof. Ihlenfeldt is also a Director at Fraunhofer IWU Chemnitz. Furthermore, he is Corporate member of the International Academy for Production Engineering (CIRP) and member of the German Academic Association for Production Technology, WGP.